Nonunit protection based on the ratio of IVRW tangent envelope area for modular multilevel converter based HVDC grid - Yao Sun; Yanfang Fan; Junjie Hou; Guobing Song (Scientific Reports)
Abstract In modular multilevel converters-based DC power grid, short faults develop rapidly and have complex characteristics. The power electronic converter has a limited ability to withstand overcurrent. So, protection needs to quickly identify the fault area in an extremely short time. Non-unit protection based on traveling waves has the advantage of rapid action, but its ability to resist fault resistance needs to be improved. To improve protection performance, a non-unit protection based on the ratio of initial fault voltage reversal wave (IVRW) tangent envelope area is proposed. First, the waveform distortion characteristics and the waveform characteristics of the IVRW at different fault locations are analyzed. Second, the tangent envelope area ratio is used to characterize the waveform distortion characteristics, which gets rid of the influence of fault resistance. Then, a fault identification criterion is constructed. And a protection scheme based on the tangent envelope area ratio is proposed by combining the start criterion and the fault pole criterion. Simulation results show that the proposed scheme has strong resistance to fault resistance and the setting value does not depend on simulation. In addition, the scheme can still effectively identify the protection area under weak boundaries and strong noise interference.